Social policy and the situation of elderly people - Krajewski, Piotr (Studia Ecologiae et Bioethicae, 2006)
We have observed great interest in the phenomenon of aging of the population and its consequences. On the hand, all who are much younger should learn how to grow old taking into account that the phenomenon of life is a dynamic process and it is not connected with the present day but the future which will come very fast, that is why, it should not find us unprepared. Some attention is paid to the problem of aging and social duty of securing old people a decent existence. It requires a change of consciousness regarding old people as well as their own consciousness. It is known that education is a constant process which is based on a fundamental human right to self-realisation. It contributes to global development of society which we are a part of. Human personal life becomes a subject of economic manipulation, thus , next to global and clear policy directed to old people, which is a central part of the family policy, increasing activity of the private people and local institutions in using and regaining educational values of the old person presence in family and social life is suggested.